Koneksi Politik dalam Dinamika Tekanan Keuangan dan Penghindaran Pajak - Arifin, Zidan Dwinanda; Mochtar, Raja Ade Fitrasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study examines the effect of financial constraints and financial distress on tax avoidance with political connections as a moderating variable in energy companies listed on the Indonesia Stock Exchange during 2022–2024. The topic is relevant because the energy sector is highly exposed to tax avoidance risks and closely linked to political actors. Secondary data were obtained from annual and financial reports and analyzed using panel data regression with the Common Effect Model (CEM). The findings reveal that financial constraints and financial distress have a negative effect on tax avoidance. Moreover, political connections strengthen the relationship between financial constraints and tax avoidance but weaken the influence of financial distress on tax avoidance. These results highlight the crucial role of political ties in shaping corporate tax strategies under financial pressure. The study provides meaningful insights for regulators and stakeholders in designing more effective and transparent tax policies.